Inovasi Colour Partograf dalam Peningkatan Kompetensi Mahasiswi Kebidanan - Yulica Aridawarni; Yuli Candra (Akademi Kebidanan La Tansa Mashiro, 2020)
Partographs are tools to monitor the progress of a first delivery and information to make clinical decisions. The role of midwives as implementers in the delivery process is an important factor for the safety of mother and baby. Situation factors that make it difficult for midwives to fill partographs are obstacles that must be resolved. The problem around childbirth is that not all midwives use partographs in every delivery assistance, not all midwives can use partographs in every delivery, not all midwives can use partographs properly in labor monitoring. One of the goals of a partograph is to record the results of observations and progress of labor by assessing the opening of the cervix through internal examination, assessing the quality of uterine contractions and decreasing the lowest part. The aim of this innovative scientific work is to design and create a Color coded partograph practice for the academy of midwifery, the basic material of mica plastic with the final results published using entrepreneurial techniques. To make it easier for midwifery students to prepare their skills and knowledge as early as possible to master and apply partographs.